Tabernaemontana divaricata leaves extract exacerbate burying behavior in mice - Raj, Chanchal (Raj Navin, 2018)
Objective: Tabernaemontana divaricata (TD) from Apocynaceae family offers the traditional folklore medicinal benefits such as an anti-epileptic, anti-mania, brain tonic, and anti-oxidant. The aim of the present study was to evaluate the effect of ethanolic extract of TD leaves on burying behavior in mice. Materials and Methods:Mice were treated with oral administration (p.o.) of ethanolic extract of TD (100, 200, and 300 mg/kg). Fluoxetine (FLX, a selective serotonin reuptake inhibitor) was used as a reference drug. Obsessive-compulsive behavior was evaluated using marble-burying apparatus. Results:TD at doses of 100, 200, and 300 mg/kg dose-dependently inhibited the obsessive and compulsive behavior. The similar results were obtained from 5, 10, and 20 mg/kg of FLX. TD and FLX did not affect motor activity. Conclusion: The results indicated that TD and FLX produced similar inhibitory effects on marble-burying behavior.